POLA PENGGUNAAN OBAT PASIEN ISPA (PNEUMONIA) RUANG RAWAT INAP RUMAH SAKIT ANUTAPURA PALU TAHUN 2021 - Andriawan; Tuldjanah, Muthmainah; Erick Budiawan (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Pneumonia is a respiratory tract infection that causes coughing, difficulty breathing, sore throat, runny nose, earache, and fever, that caused by various kinds of bacteria, viruses, and fungi. This study aims to determine the accuracy of drug use in pneumonia patients based on indicators of the right dose, the right frequency and the right indication of the drug in the Inpatient Room of Anutapura Hospital Palu. This study was carried out using a cross sectional where data were collected retrospectively based on medical record data of ARI (Pneumonia) patients using a minimized sampling technique namely 30 samples based on the inclusion criteria. The results of this study showed that the most pneumonia patients were male, as many as 20 patients (67%). Meanwhile, based on the age range, the most age group affected namely the age of 1- 5 years, as many as 21 patients (70%). The results also showed that the most widely pneumonia drug used were antibiotics (32%), analgesics antipyretics (22%), corticosteroids (17%), and mucolytics (13%). This is in accordance with the recommendation of therapy from the Director General of Community and Clinical Bimfar 2005.